Coverage of Suicides in Klaipėda‘s Newspapers During the Period from 1991 to 2004 - Gedutienė, Reda; Maskoliūnaitė, Laura (Sociologija. Mintis ir veiksmas, 2005)
The paper examines the peculiarities of reporting suicides in Klaipėda‘s newspapers during the period from 1991 to 2004. The articles were analyzed using 28 features evaluation scheme (according to Gailienė, Trofimova 1999). The qualitative and quantitative analyses of articles covering suicides revealed that majority of them do not satisfy the recommendations for suicides to be reported in media. Main newspapers in Klaipėda almost do not pay any attention to suicide prevention and help. Moreover, the articles practically do not publish statistical data and results based upon scientific research.
Keywords: suicide coverage; mass-media; newspaper